A comparison of thermal maturity parameters between freely extracted hydrocarbons (Bitumen I) and a second extract (Bitumen II) from within the kerogen matrix of Permian and Triassic sedimentary rocks - Nabbefeld, Birgit; Grice, Kliti; Schimmelmann, A.; Summons, R.; Troitzsch, U.; Twitchett, R. (Elsevier Science, 2010)
In this study we compared various maturity dependent aromatic, steroid and triterpenoid hydrocarbonratios in bitumens that are freely extractable from sedimentary rocks (Bitumen I) with those in second extracts that comprised hydrocarbons closely associated with the kerogen/mineral matrix (Bitumen II).Bitumen II was released through kerogen isolation and demineralisation using HCl and HF/H3BO3. Thesamples studied, although of similar age, come from different localities. They represent a range of faciesand two kerogen types (II and III), and all were deposited under marine conditions. The results show that the more stable b isomers of methylnaphthalene (MN) and methylphenanthrene (MP) are relatively more abundant in Bitumen II. The difference between the methylnaphthalene ratio (MNR) of Bitumens I and II, when plotted against the ratio of clay to total organic carbon (clay/TOC), gives an excellent correlation (R2 = 0.88). The highest clay/TOC ratio corresponds with the biggest difference in MNR for the respective bitumens, consistent with the more stable b isomers being preferentially retained within the clay/kerogen matrix. Since the b MP isomers are higher in Bitumen II than in Bitumen I, it was anticipated that their methylphenanthrene index (MPI-1) values, a commonly used measure of thermal maturity, would also be different. For most samples, the measured MPI-1 in Bitumen I is generally higher than that in Bitumen II (except for three samples), thus showing a bias towards a lower thermal maturity for the second extract. The opposite is true of the b/a MP ratio and MNR. This may be attributed to the fact that phenanthrene (P), which is part of the denominator in MPI-1, is more stable than its methylated counterparts.Steroid and triterpenoid maturity parameters also showed differences between the two extracts, with C27 diasterane/sterane and Ts/(Ts + Tm) being higher in Bitumen I. Only the former parameter is positively correlated with the clay/TOC ratio, suggesting that clay content probably influences the diagenetic transformation of steroid precursors to diasteranes. The observed differences between the maturity parameters of Bitumen I and Bitumen II may be especially important in sedimentary rocks that contain high percentages of clay minerals.